Strategic Decision-Making and Implementation in Public Organizations in the Gulf Cooperation Council: The Role of Procedural Rationality - Al-Hashimi, K. (Wiley, 2021)
Yes === Based on Herbert Simon's conceptualization of bounded rationality, this study develops and tests an integrative model of the strategic decision-making process (SDMP) and outcomes in public organizations. The model integrates different SDMP dimensions—procedural rationality, intuition, participation, and constructive politics—and examines their impacts on the successful implementation of strategic decisions. Additionally, it analyzes the influence of implementation on the overall outcomes of strategic decisions. The model was tested with multi-source data on 170 strategic decisions collected from senior executives working in 38 public organizations in Qatar—a context in which studies on decision-making are rare. With the exception of intuition, this study shows a positive impact of all SDMP dimensions on the successful implementation and outcomes of strategic decisions. Successful implementation fully mediates the relationships between procedural rationality, participation, and constructive politics and the outcomes of strategic decision. === The full-text of this article will be released for public view at the end of the publisher embargo on 6 Nov 2023.